Leading with Prophetic Values: How Islamic Leadership Transparency Cultivates Organizational Trust - Refika Refika; Mukhyar Mukhyar; Irjus Indrawan; Willson Gustiawan; Diani Ayu Pratiwi (JURNAL AL-TANZIM, 2026)
This study aims to analyze the implementation of Islamic leadership transparency, its role in building trust-based management, and the organizational factors that support and hinder its implementation. This study used a qualitative approach with a case study method at two Islamic higher education institutions in Indonesia. Data were collected through in-depth interviews, non-participant observation, and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and conclusion drawing, with validation through source triangulation and member checking. The results show that Islamic leadership transparency is realized through the internalization of prophetic values, namely tabligh, ṣidq, amanah, and fatānah, which contribute to building organizational trust by strengthening procedural justice, interactional justice, and distributive justice. The implementation of transparency is supported by the integrity of leaders, open communication, and a strong Islamic organizational culture. Conversely, a hierarchical bureaucratic structure and limited access to information are inhibiting factors in its implementation. This research highlights the importance of developing governance in Islamic educational organizations based on transparency, accountability, and prophetic values to strengthen trust and the effectiveness of organizational management on a sustainable basis.